ELASTISITAS EKSPOR SEKTOR PERTANIAN TERHADAP IPM KETIMPANGAN, KEMISKINAN, TPT DAN PDRB PROVINSI SUMATERA UTARA - Lumban Gaol, Roberto Anggiat Iron; Sukadana, I Wayan (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.12.NO.12.TAHUN.2023, 2023)
Indonesia is an agricultural country and has a large abundance of natural resources, especially in the agricultural sector. The abundance of resources in the agricultural sector is also balanced by high economic growth. However, at the same time, people's welfare is still relatively low. It is feared that there is a natural resource curse phenomenon in resource management in Indonesia. The purpose of this study was to determine the elasticity of exports of the agricultural sector to welfare indicators in North Sumatra Province. The data source is secondary data using time series data for 20 years and cross section data as many as 7 variables that produce 140 observations. The analytical technique used in this study is the distribution lag model. The results showed that the elasticity of exports of the agricultural sector to indicators of public welfare in the province of North Sumatra is inelastic. Exports of the Agricultural Sector also have a significant effect on indicators of inequality and the open unemployment rate when viewed from the side of the trend for 20 years. The community is expected to participate in every poverty alleviation effort, especially through the contribution of income to the income of poor households.